Algorithm of echocardiography in pregnant women - S. G. Gorokhova; T. E. Morozova; A. A. Arakelyants; E. A. Barabanova; E. G. Dyakonova (Российский кардиологический журнал, 2018)
Pregnancy is a physiological condition that takes a defined period of time in a woman’s life. For nine months, the mother’s heart works under conditions of daily additional load, which is necessary to ensure placental blood flow. In this regard, structural and functional adaptation of the heart develops in a healthy woman with a normal pregnancy. A pregnant woman with some heart diseases is less likely to adapt. That leads to greater susceptibility to stress resulting in pathological changes of pregnancy. In addition, each pregnancy may develop new heart diseases, which in some cases may be relatively innocent, but in others — fatal. In this regard echocardiography (EchoCG) is a necessary procedure for assessing a woman’s health status that needs before bearing a fetus, during and after pregnancy.